OPTIMIZATION OF THERMOPHYSICAL PROPERTIES, COMBUSTION PERFORMANCE AND HARMFUL EXHAUST GASES OF BIODIESEL FUEL WITH NANOPARTICLE ADDITIVES - MEHMET CELIK; CIHAN BAYINDIRLI (Journal of Engineering Studies and Research)
Increasing use of diesel products causes decrease of oil reserves, global warming, increase in the world average and adverse effects on human health and the environment. Emissions from combustion in engines are directly related to the quality, properties and combustion characteristics of the fuel. Since the physical and chemical properties of the fuel affect the atomization characteristics, it is important for increasing the combustion efficiency. The most important fuel properties affecting the combustion of diesel fuel are cetane number, viscosity, density and calorific value. There are many applications in improving the chemical and physical properties of fuel. One of them is nanoparticle (NPs) additives adding in fuel. In this study, it was aimed to improve fuel properties with optimum additive ratio by adding CeO2, TiO2 and Co3O4 nanoparticle additives into biodiesel which are produced from cotton and canola oil. The effects of NPs additives in fuel properties such as viscosity, density, lower calorific value and flash points were investigated.